Effect of transient ulnar artery compression on radial artery diameter - Yilmaztepe, Mustafa Adem (Exp Ther Med, 2018)
The transradial approach is widely preferred in coronary procedures. A small radial artery diameter (RAD) is the most important factor affecting successful access. Various maneuvers and medications have been used to increase the RAD and thereby facilitate RA cannulation. Ulnar artery compression (UAC) for 30 min has been indicated to be effective in increasing the RAD and facilitating RA access. The aim of the present preliminary study was to assess the effect of transient UAC for 1 min on the RAD. A total of 151 patients were included in the present study. RA ultrasonography was performed at the level of the wrist. The UA was compressed for 1 min. The RAD was measured at baseline, at the end of UAC and at 1 min thereafter. The results indicated that the RAD was significantly smaller in diabetic vs. non-diabetic patients (2.35±0.43 vs. 2.50±0.39 mm, P=0.024) and in women vs. men (2.25±0.38 vs. 2.56±0.38 mm, P<0.001). At the end of UAC, the RAD was increased compared with that at baseline (2.45±0.41 vs. 2.62±0.41 mm, P<0.001), but it started to decrease thereafter, and the RAD measured at 1 min after stopping UAC was significantly smaller (2.62±0.41 vs. 2.55±0.40 mm, P<0.001), while remaining significantly larger than that at baseline (P<0.001). The RA peak systolic flow velocity also increased significantly during UAC (35.3±8.9 vs. 60.3±19.2 cm/sec; P<0.001). In conclusion, Transient UAC for 1 min significantly increased the RAD and the peak systolic flow velocity. Further studies with clinical endpoints are required for further exploration of the feasibility of this approach.